The use of methyl ethyl ketone in nitric acid leaching processes for enhancement of Ag recovery from used X-ray films - Jo, H.; Yoo, Kyoungkeun; Kim, S.; Alorro, Richard (Japan Institute of Metals and Materials, 2018)
A feasibility study was carried out to improve conventional recycling processes of used X-ray film, where silver was recovered mainly by concentrated nitric acid leaching. In the X-ray film, an emulsion layer containing silver is attached to polyester film base, and the enhancement of Ag leaching was expected by separating the emulsion layer from the polyester film base using methyl ethyl ketone (MEK), because the separation could increase the contact surface between nitric acid and Ag in the emulsion layer. First, the separation behaviors using MEK were investigated and the separation efficiencies of the emulsion layer increased with increasing temperature but decreasing film size and pulp density. The separation efficiency increased to 100% in MEK solution within 3 min under the following conditions; temperature 50°C; setting agitation speed 400 rpm; pulp density 50 g/L; film size 1 © 1 cm. In the followed nitric acid leaching test, the leaching result using the separated emulsion layer showed higher leaching efficiency than that using the unseparated X-ray film. Second, the effect of adding MEK to nitric acid leaching on the leaching efficiency of Ag was investigated by considering the amount of MEK added and temperature as experiment factors. The leaching efficiency of Ag increased with increasing the amount of MEK to 5%, but further addition of MEK to 7% rather reduce the leaching efficiency. With 5% of MEK addition, the leaching efficiency of Ag increased up to 95.9% in 120 min at 50°C whereas it increased and then decreased to 2.7% in the test at 70°C due to the formation of AgCl. These results indicate that the leaching efficiency of Ag could be enhanced using MEK in the nitric acid process for the recovery of Ag from the used X-ray film.